ANALISIS FAKTOR FAKTOR YANG BERPENGARUH TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Rudy Fernando; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
This study aims to analyze and provide empirical evidence of debt default, opinion shopping, audit opinion the previous year, and disclosure on the probability of receiving going concern opinion. Hypothesis proposed (1) debt default effect on acceptance going concern opinion, (2) opinion shopping influence on acceptance going concern opinion,(3) audit opinion the previous year influence on acceptance going concern opinion,(4) disclosure affect the probability of accepting the opinion of going concern.             This study used 23 manufacturing companies listed on the Indonesian Stock Exchange (BEI) in the year 2008 to 2013, sample obtained by purposive sampling. Data were analyzed using logistic regression anylisis            The results of this research showed that debt default, and audit opinion the previous year have a significant influence on acceptance going concern opinion.While the other factors, opinion shopping and disclosure are not proven having a significant influence for Timeliness.